JAR VESSELS FROM THE KURA-ARAXES SITES IN DAGESTAN: A TYPOLOGICAL AND TECHNOLOGICAL STUDY - Budajciev, Arsen Lahmanovic; Sajpudinov, Murad Sahbanovic (History, Archeology and Ethnography of the Caucasus, 2025)
This article presents a typological and technological analysis of jar vessels from Early Bronze Age sites in Dagestan associated with the Kura-Araxes cultural-historical community. The jars are classified according to key morphological features: body shape, rim form, and the presence of handles. This classification yields six types, with Type II further divided into two subtypes (A and B). Analogies and parallels for these jars are drawn not only from regions of the Caucasus adjacent to Dagestan but also from more distant areas, including Eastern and Central Anatolia and Northwestern Iran, where Kura-Araxes sites have produced similar vessels. Applying the technical and technological analysis method developed by A.A. Bobrinsky, we obtained data on the recipes (compositions) of the molding pastes used for these jar vessels. Vessels from sites in Mountainous Dagestan were produced using a single primary recipe: clay + chamotte + organic solution. In contrast, vessels from Primorsky Dagestan employed two recipes: clay + chamotte + manure (77.8%) and clay + chamotte + organic solution (22.2%). These findings enabled the reconstruction of pottery traditions in jar production, which proved to be distinct between the two regions. This distinction suggests the persistence in Mountainous Dagestan of an older, possibly Eneolithic, technological tradition in pottery-making, alongside influences from the Kura-Araxes potters of Primorsky Dagestan. The results of this study can contribute to investigations of Kura-Araxes pottery across the Caucasus and the Middle East.